Klebsiella pneumoniae hijacks the Toll-IL-1R protein SARM1 in a type I IFN-dependent manner to antagonize host immunity. - Carty, Michael; Bowie, Andrew (My University, 2022)
Many bacterial pathogens antagonize host defense responses by translocating effector proteins into cells. It remains an open question how those pathogens not encoding effectors counteract anti-bacterial immunity. Here, we show that Klebsiella pneumoniae exploits the evolutionary conserved innate protein SARM1 to regulate negatively MyD88- and TRIF-governed inflammation, and the activation of the MAP kinases ERK and JNK. SARM1 is required for Klebsiella induction of interleukin-10 (IL-10) by fine-tuning the p38-type I interferon (IFN) axis. SARM1 inhibits the activation of Klebsiella-induced absent in melanoma 2 inflammasome to limit IL-1β production, suppressing further inflammation. Klebsiella exploits type I IFNs to induce SARM1 in a capsule and lipopolysaccharide O-polysaccharide-dependent manner via the TLR4-TRAM-TRIF-IRF3-IFNAR1 pathway. Absence of SARM1 reduces the intracellular survival of K. pneumoniae in macrophages, whereas sarm1-deficient mice control the infection. Altogether, our results illustrate an anti-immunology strategy deployed by a human pathogen. SARM1 inhibition will show a beneficial effect to treat Klebsiella infections.
PUBLISHED
Keywords: AIM2 inflammasome; CP: Immunology; CP: Microbiology; Klebsiella pneumoniae; SARM1; type I IFN